The Impact of Financial Literacy, Investment Knowledge, and Investment Motivation on Investment Decisions - Handini, Sri (West Science Journal Economic and Entrepreneurship, 2024)
This study investigates the relationship between management students' investment decisions and their financial literacy, knowledge, and motivation at Dr. Soetomo University in Surabaya. A total of 308 students from this academic program were chosen for the study using purposive sampling techniques, guaranteeing that the study's population is representative of the student body. We distributed carefully crafted questionnaires for data collection through Google Forms as part of the methodology used in this study. Purposive sampling methods are used to ensure the student body is well represented. We meticulously examined the gathered data using a variety of statistical methods. Among these were evaluations of reliability and validity, analyses of multiple linear regression, tests of classical assumptions, evaluations of correlation coefficients, and F and t-tests. This study uncovered insightful relationships between students' financial literacy, investment knowledge, motivation, and investment decisions. The study found no statistically significant impact of financial literacy on investment decisions, contrary to expectations. The results of the study, however, highlighted the importance of respondents' unique investment knowledge and motivation in molding their investment choices. Students' level of financial literacy, investment knowledge, and investment motivation significantly impacted their investment decisions as a whole. By considering these factors in context, we can better understand the complex dynamics at work when management students at Dr. Soetomo University make investment decisions.